Evaluation: A Qualitative Pilot Study of Novel Information Technology Infrastructure to Communicate Genetic Variant Updates - Klinkenberg-Ramirez, Stephanie; Neri, Pamela M.; Volk, Lynn A.; Samaha, Sara J.; Newmark, Lisa P.; Pollard, Stephanie; Varugheese, Matthew; Baxter, Samantha; Aronson, Samuel J.; Rehm, Heidi L.; Bates, David W. (Applied Clinical Informatics, 2016)
Partners HealthCare Personalized Medicine developed GeneInsight Clinic (GIC), a tool designed to communicate updated variant information from laboratory geneticists to treating clinicians through automated alerts, categorized by level of variant interpretation change.The study aimed to evaluate feedback from the initial users of the GIC, including the advantages and challenges to receiving this variant information and using this technology at the point of care.Healthcare professionals from two clinics that ordered genetic testing for cardiomyopathy and related disorders were invited to participate in one-hour semi-structured interviews and/ or a one-hour focus group. Using a Grounded Theory approach, transcript concepts were coded and organized into themes.Two genetic counselors and two physicians from two treatment clinics participated in individual interviews. Focus group participants included one genetic counselor and four physicians.Analysis resulted in 8 major themes related to structuring and communicating variant knowledge, GIC’s impact on the clinic, and suggestions for improvements. The interview analysis identified longitudinal patient care, family data, and growth in genetic testing content as potential challenges to optimization of the GIC infrastructure.Participants agreed that GIC implementation increased efficiency and effectiveness of the clinic through increased access to genetic variant information at the point of care.Development of information technology (IT) infrastructure to aid in the organization and management of genetic variant knowledge will be critical as the genetic field moves towards whole exome and whole genome sequencing. Findings from this study could be applied to future development of IT support for genetic variant knowledge management that would serve to improve clinicians’ ability to manage and care for patients.Citation: Klinkenberg-Ramirez S, Neri PM, Volk LA, Samaha SJ, Newmark LP, Pollard S, Varugheese M, Baxter S, Aronson SJ, Rehm HL, Bates DW. Evaluation: A qualitative pilot study of novel information technology infrastructure to communicate genetic variant updates.
Keywords: Clinical informatics applications; clinical decision support; genetics; personalized medicine; laboratory software